Towards delighting your customer / Hamidah Kassim - Kassim, Hamidah (Perpustakaan Tun Abdul Razak, UiTM, 2004)
Giving your customers more than they expected means delighting them. Delight is far more than satisfying. You must plan on producing and delivering high quality products and services. Remember that you are not just selling your customers products/ services, you are selling them satisfaction or value.